An Analysis of the Current Trend of Export Earnings from Plastic Products: A Case Study of Bangladesh - Afrin, Sazia; Lima, Kiptia Akhter (Asian Journal of Empirical Research, 2015)
Among the few sectors with diversified products, Plastic industry is contributing in the GDP at an increasing rate. Despite being relatively new to the export basket and facing other constraints like lack of skilled manpower, developed infrastructure, administrative institution it has a great potential for growth. This paper is an attempt to analyze the current situation of the export earnings from the plastic sector. A log-linear model is developed to see the dependence of GDP on Plastic Export Earnings. It reveals that if plastic export earnings increase by 1%, GDP goes up by .75%. Some initiatives are proposed to promote growth of the very sector such as relocation of the industry where environmental risks are low, government intervention on administrative issues, proper recycling etc.